Persepsi Masyarakat Terhadap Revitalisasi Pasar Dupa Kencana Pekanbaru - suci, afred (Komunitas Manajemen Kompetitif, 2016)
Abstract: Study held in Dupa Kencana Market Pekanbaru in order to analyze consumer’s perception towards traditional market and its impact to revitalization of Dupa Kencana market. Population consists of Pekanbaru society as the regular consumers. Respondent numbers determined by Hair theory and consists of 70 respondents. Variable used are perception as independent, while the revitalization used as dependent. Data analyzed by using descriptive and simple regression analysis. Study reveals that consumer’s perception is still negative but it doesn’t significantly raises the intention of them in order to have Dupa Kencana market revitalized. The only revitalization they want is merely zoning revitalization, instead of total revitalization or relocation Keywords: Perception, Revitalization, Traditional Market